Strategi Meningkatkan Resiliensi Melalui Afirmasi Positif Pada Remaja Panti Asuhan Al-Hikmah - Sania Qotrun Nada; Rachil Najma Shifa’; Siti Hikmah (Lembaga Pengembangan Kinerja Dosen, 2024)
Life in orphanages presents various psychological challenges for adolescents, including low self-confidence and limited emotional support. This study aims to improve the resilience of adolescents at Al-Hikmah Orphanage through positive affirmation intervention. The positive affirmation technique is a positive statement written consciously and confidently, which is proven to be effective in overcoming negative thinking, building self-confidence, and creating better psychological conditions. This study used a participatory intervention design involving 10 adolescents aged 16-18 years. The activities included initial data collection through pre-test, introduction to the concept of resilience, emotion management training, problem solving exercises, and decision making. Evaluation was conducted using a post-test to measure changes in resilience, followed by documentation of program results and a final report. The results of the intervention showed significant improvements in adolescents' self-confidence, ability to write life goals, and positive mindset. The main supporting factors were the enthusiasm of the participants, the active support of the caregivers, and the conducive environment of the home. However, some barriers such as deep traumatic experiences, limited experts, and short program duration were challenges that affected the intervention results. Positive affirmation can effectively improve adolescents' resilience by building positive mindsets, reducing anxiety, and strengthening adaptation to stress. For optimal impact, this program needs to be combined with intensive psychological counseling and implemented in a sustainable manner. This approach can also be adapted in other orphanages by adjusting the needs of the local community